Burnout and Engagement in Health Profession Students: The Relationships Between Study Demands, Study Resources and Personal Resources. (19th January 2015) - Robins, Tamara G.; Roberts, Rachel M.; Sarris, Aspa
Abstract : Burnout has been related to increased suicidal thoughts, lower self-esteem and dropout in university students. Engagement in students, however, has been underexplored. This study uses the Job Demands-Resources (JD-R) model and the Conservational of Resources (COR) model to contribute to the knowledge about burnout and engagement in health profession university students. In particular, the role of personal resources, including psychological flexibility, was examined. Participants were 260 nursing, social work, occupational therapy and psychology students from 10 Australian universities. Regression analyses were used to test the JD-R model with a health profession student sample. The model was extended by including personal resources and testing mediation and moderation hypotheses. Personal resources contributed significant additional variance to the model. Mediation effects of study demands and resources with psychological flexibility were found, while moderation effects were not. The results indicate the validity of the JD-R model in a health profession student population and the important role of personal resources. Further design and evaluation of interventions targeting personal resources and study demands and resources are indicated.